EFEKTIVITAS INTERVENSI PANGAN FUNGSIONAL BERBASIS PUDING BUAH LONTAR (BORASSUS FLABELLIFER) DAN EKSTRAK DAUN KELOR TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL - Khusnul Khotimah; Defi Kristina Sari (Forind Press, 2026)
Anemia in pregnancy remains a major public health problem in developing countries. Iron supplementation programs are widely implemented; however, their effectiveness is often limited by low compliance. Therefore, alternative interventions based on functional foods that are more acceptable and sustainable are needed. This study aimed to evaluate the effectiveness of palm fruit pudding (Borassus flabellifer) fortified with Moringa leaf extract (Moringa oleifera) in improving hemoglobin levels among pregnant women. A quasi-experimental study with a pretest-posttest control group design was conducted involving 30 pregnant women in their second and third trimesters, divided into an intervention group (n=15) and a control group (n=15). The intervention group received fortified pudding for 30 days, while the control group received nutritional education and iron supplementation. Data were analyzed using paired t-test, independent t-test with a significance level of p < 0.05. The results showed that both groups experienced an increase in hemoglobin levels; however, the increase was greater in the intervention group compared to the control group. The mean hemoglobin change in the intervention group was 1.32 ± 0.13 g/dL, while in the control group it was 0.95 ± 0.19 g/dL, with a statistically significant difference (p < 0.001). It can be concluded that palm fruit pudding fortified with Moringa leaf extract is effective in increasing hemoglobin levels in pregnant women and has potential as a local functional food-based intervention for anemia prevention.